ANALISIS KESALAHAN ASPEK “LE” PADA MAHASISWA ANGKATAN 2023 PRODI PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Utari, Eti; Veronica, Tjen; Lusi, Lusi (Universitas Tanjungpura, 2026)
The dynamic auxiliary word“了”is a relatively special word, mainly because it has various meanings that are determined by the sentence and its position. This study investigates the lack of understanding among students regarding the use of the dynamic auxiliary word “了”. The purpose of this study is to further understand the usage of this word and to identify the errors made by students and the factors that cause these errors, in order to make a contribution to Chinese language teaching. This study uses a qualitative research method, specifically a testing method that collects information for evaluating Chinese language teaching by administering a Chinese language test to learners. The research subjects are students from the 2023 batch of the Chinese Language Education Universitas Tanjungpura. Study concludes that the error types can be categorized into four types: addition errors, substitution errors, omission errors, and sequence errors. The main reasons for these errors are negative transfer from the native language. The analysis results show that students still cannot use the dynamic auxiliary word“了”correctly, mainly because students no fully understand the usage of this word.